The first material made for air pollution control able to sequestrate fine and ultrafine air particulate matter. (February 2020) - Zanoletti, Alessandra; Bilo, Fabjola; Federici, Stefania; Borgese, Laura; Depero, Laura E.; Ponti, Jessica; Valsesia, Andrea; La Spina, Rita; Segata, Monica; Montini, Tiziano; Bontempi, Elza
Highlights: A new silicate-based material (SUNSPACE) is proposed to provide air remediation. SUNSPACE synthesis is also slightly modified to promote its application in building. SUNSPACE capability in PM trapping is investigated in wet and dry conditions. Abstract: Air pollution accounts as a critical environmental issue in different populated cities. With the introduction of smart cities concept, suitable measures to reduce people exposition to pollutants must be part of the policies for a suitable urban development. Generally urban policy makers have proposed some restrictions (for example for traffic), that were resulted insufficient. Then probably, different approaches may be considered to face the air pollution problem. This paper proposes a new porous hybrid material (SUNSPACE) based on the use of industrial silicate minerals and alginate materials to promote PM sequestration in urban areas. It was designed to be applied as a coating on all available external cities surfaces. The synthesis conditions were slightly modified, with respect to the original material, to avoid thermal treatment, and make the material directly applicable. SUNSPACE was characterized by using different techniques: nitrogen physisorption, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Results identify the presence of ink-bottle pores shape, suitable to sequestrate nano and micro PM. Moreover, PM reduction in the atmosphere generally occurs as a consequence of wet or dry deposition conditions, monodisperse Fe3 O4 nanoparticles and indoor/outdoor exposure were used to investigate the ability of SUNSPACE in ultrafine PM sequestration.